Pengruh Metode Cooperative Learning Tipe Numbered Head Together (NHT) Terhadap Hasil Belajar Matematika Siswa Kelas IV SDN Muhammadiyah 1 Kota Tangerang - Ahmad Amarullah; Desri Arwen; Enawar Enawar (Jurnal Pendidikan Matematika : Judika Education, 2022)
The purpose of this study was to determine whether there was an influence of the Cooperative Learning Type Numbered Head Together (NHT) method on the mathematics learning outcomes of fourth grade students at SDN Muhammadiyah 1 Tangerang City. The sample in this study used a simple random sampling technique. The method used is an experiment using an experimental class and a control class. Data collection techniques use learning outcomes in the form of formative tests conducted at the beginning and end of the study using the t test. So that means the null hypothesis (Ho) is rejected and the working hypothesis (H1) is accepted. The results of the calculations carried out turned out that the learning outcomes of the experimental class using the Numbered Head Together (NHT) Cooperative Learning method were better than the learning outcomes of the control class so that the null hypothesis (Ho) was rejected, thus the working hypothesis was accepted, meaning that there was an influence of the numbered head cooperative learning method. together (NHT) on the results of learning mathematics for fourth grade students at SDN Muhammadiyah 1 Tangerang City. So it can be concluded that there is a significant effect of the Cooperative Learning Type Numbered Head Together (NHT) method on mathematics learning outcomes in fourth grade students at SDN Muhammadiyah 1 Tangerang City. Key Word: Cooperative Learning Method, Numbered Head Together (NTH), Student Learning Outcomes